Wandering poets and the dissemination of Greek tragedy in the fifth and fourth centuries BC - Stewart, Edmund (2013)
This work is the first full-length study of the dissemination of Greek tragedy in the earliest period of the history of drama. In recent years, especially with the growth of reception studies, scholars have become increasingly interested in studying drama outside its fifth century Athenian performance context. As a result, it has become all the more important to establish both when and how tragedy first became popular across the Greek world. This study aims to provide detailed answers to these questions.